Small intestinal bacterial overgrowth syndrome and systemic inflammation in pathogenesis of hemodynamic changes at liver cirrhosis - R. V. Maslennikov; A. A. Driga; K. V. Ivashkin; M. S. Zharkova; M. V. Mayevskaya; Ch. S. Pavlov; M. G. Arslanyan; N. B. Musina; Ye. N. Berezina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate the impact of small intestinal bacterial overgrowth (SIBO) to development of hemodynamic disorders at liver cirrhosis (LC). Material and methods. Original study included 50 LC patients and 15 generally healthy controls. Lactulose hydrogen breath test, serum level of C-reactive protein and cardiac ultrasound with simultaneous blood pressure (BP) and heart rate measurement, estimation of basic hemodynamic scores: mean blood pressure (MBP), cardiac output (CO), total peripheral vascular resistance (TPVR) were investigated in all patients. Results. LC patients with SIBO as compared to LC patients without SIBO had lower mean blood pressure (82.7±9.0 mm Hg vs 92.0±14.0 mm Hg) and TPVR (16.4±4.4 mm Hg × min/l vs 21.3±5.3 mm Hg • min/l), higher CO (5.38±1.41 l/min vs 4.52±1.03 l/ min) and serum C-rp (SIBO - 1.2÷10.5÷16.5 mg/l vs 0.6÷2.8÷9.1 mg/l). The presence of SIBO led to similar changes only at decompensated LC. At the same time no significant hemodynamic disorders were revealed at decompensated LC without SIBO and compensated LC irrespective of SIBO. At LC significant correlation of serum C-rp to TPVR (r=-0.367; p=0.009) and CO (r=0.313; p=0.027) was found, but not to mean BP (r=-0.227; p=0.113). Conclusion. SIBO at LC plays important role in vasodilation, arterial hypotension and hyperdynamic circulation. As these hemodynamic disorders aggravate the course of portal hypertension, the treatment of SIBO may reduce severity of the latter.